Characterization of Hesperidin-PEG 1000 Solid Dispersion Prepared by Freeze Drying Method - Aga Mikail; Aditya Trias Pradana; Endang Wahyu Fitriani; Agnes Nuniek Winantari; Astridani Rizky Putranti; Xandramela Limala Alicya Junaidi Lee (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2026)
Hesperidin is a disaccharide-derivative bioflavonoid in BCS class II, insoluble in water but soluble in propylene glycol and polyethylene glycol, and its poor aqueous solubility may impair bioavailability, necessitating modification via solid dispersion. In this study, a hesperidin–PEG 1000 system was prepared at 1:1 and 1:6 hesperidin:PEG 1000 ratios using freeze‑drying. The systems were characterised for crystallinity, thermal behaviour, vibrational transitions, and particle morphology. PXRD patterns recorded over 2θ = 5–40° showed that both solid dispersions retained the main diffraction peaks of pure hesperidin with reduced intensities, indicating preservation of a predominantly crystalline structure. DSC thermograms revealed a hesperidin melting peak at 261.0 °C for the pure drug, which shifted to 248.6 °C and 241.0 °C for the 1:1 and 1:6 systems, respectively, without disappearance of the drug melting event. Data from FTIR and SEM further indicated only minor molecular interactions and limited morphological changes, and the characterisation results for both ratios were essentially identical. Taken together, these findings indicate that freeze‑drying hesperidin with PEG 1000 under the applied conditions did not convert hesperidin into an amorphous, molecularly dispersed solid dispersion, but yielded a predominantly crystalline, hesperidin‑dominated system with minimal PEG 1000 incorporation.